Prevalence and risk factors of prehypertension and hypertension in Algeria - Abdellatif Moussouni; Adel Sidi-yakhlef; Houari Hamdaoui; Amaria Aouar; Djamel Belkhatir (BMC, 2022)
Abstract Background Hypertension, also referred to as the silent killer, is known to be one of the most common chronic diseases in the world today. This study aimed to identify the prevalence and risk factors of prehypertension and hypertension among Algerian population. Methods This is a descriptive cross-sectional epidemiological study involving individuals aged 18 to 69 years old who were identified in the database of the national survey on non-communicable diseases (NCDs) risk factors conducted in Algeria between 2016 and 2017 using the World Health Organization's (WHO) STEPwise approach. Differences in prevalence between normotensives, prehypertensives and hypertensives were assessed using the chi-square test. We also looked at the role of numerous socio-demographic, economic, geographical, and behavioural factors in blood pressure status using a logistic regression model. Results The prevalence of prehypertension and hypertension was 36.2% (95% confidence interval: 35.2-37.5%) and 31.6% (95% CI: 30.5-32.7%) respectively. Prehypertension was shown to be substantially higher in males than in women, while hypertension was found to be higher in females compared to men. In addition, both sexes had a rise in the prevalence of blood pressure as they grew older. A according to multivariate logistic regression analysis, the main common risk factors for prehypertension and hypertension were ageing, obesity, and abdominal obesity. Moreover hypercholesterolemia, and marital status (separated/divorced) were correlated to hypertension. Conclusion Prehypertension and hypertension are high and epidemic in Algeria. Therefore, the urgent quantification and monitoring of their risk factors becomes a necessity to plan appropriate preventive measures, in order to fight against NCDs in general.